Why Chinese Non-Financial Firms Hedge? An Empirical Study on the Determinants of Corporate Hedging - Li, Xinyuan (2022)
With the rapid development of China's financial markets and the internationalisation of the RMB, Chinese firms are increasingly exposed to default risk and foreign exchange risk, and hence the use of derivatives for hedging as a risk management approach is increasingly used by Chinese firms. Using a unique dataset manually collected from company annual reports, this study examines the question of what the determinants of hedging for Chinese companies are, using a sample of 307 non-financial Chinese companies listed on the Hong Kong Stock Exchange from 2017 to 2020.